Las características y el desarrollo de la economía popular: Un modelo formal con evidencia etnográfica - Joaquín Morales; Valeria Salinas (Institute for Advanced Development Studies (INESAD), 2018)
– We explore reasons underlying the economic prosperity of certain popular merchants in Bolivia. Even if economics often associates popular merchants with poor economic performance and low productivity, anthropological evidence shows the existence of large fortunes in the bolivian popular economy (Tassi et al., 2013). We develop a formal model which traces back the origin of this prosperity in the coopetitive capacity (competitive plus cooperative) of popular merchants built upon the sharing of input costs. We argue that the coopetitive capacity of these actors is based on social networks of godfatherhood weaved at popular celebrations, which we document with ethnographic evidence.
Keywords: O17; D02; D24; 330; informal economy; popular economy; club theory; collective action